Early nutrition, development and health: evolutionary perspectives on the metabolic syndrome - Kuzawa, Christopher (Henry Stewart Talks, 2007)
The Developmental Origins of Health and Disease, The thrifty genotype hypothesis, Metabolic scaling in mammals, Energy partitioning in humans, The developmental bottleneck of weaning, Baby fat as a brain buffer, How fat and insulin resistance protect the brain, Why prenatal undernutrition induces the metabolic syndrome, Implications for adaptation and global disease change
Reviewed at 2020/08/16